Drug-induced agranulocytosis: Case series - Čolović Nataša R.; Leković Danijela R.; Stojković-Lalošević Milica LJ. (Hospital Pharmacology, 2018)
Introduction: Agranulocytosis is a life-threatening disorder characterized by disappearance of granulocytes from peripheral blood or decrease of peripheral neutrophil count below 0.5x109 /l. It frequently occurs as idiosyncratic adverse drug reaction. It occurs especially in association with the use of antithyroid drugs, metamizole, aminopyrine and clozapine. The patients usually present with severe acute infections and sepsis. With modern management of broad-spectrum antibiotics and hematopoietic growth factors (G-CSF) the prognosis has been significantly improved. Methods and results: We present 15 patients with drug-induced agranulocytosis, discuss the criteria for diagnosis, management and prognosis. Median patients age was 36 years (ranging from 25 to 61 years). The male/female ratio was 2/13. Underlying diseases were found in 10/15 (66.6%) patients, consisting of hyperthyreosis in 7 (46.6%) patients, mental disorders in 2 patients (13.3%) and in 1 (6.6%) patient suffering from perianalfistula. Nadir median neutrophil count was 0.3x109 /l, range 0-0.5x109 /l, hemoglobin was between 104 and 128 g/L, anaemia was present in 6 (54.5%) patients, platelet count was between 170 and 230x109 /l. The treatment consisted of broad spectrum antibiotics, hematopoietic growth factor in 10, and antimycotic fluconazole in 3 patients. The outcome was favorable in 14 (93.3%) patients and 1 patient who had thyreotoxic crisis and agranulocytosis died. After 4 months, 1 (6.6%) patient, who had a complete recovery from agranulocytosis, developed an acute myeloid leukemia and died. Conclusions: Drug-induced agranulocytosis is a rare haematological complication, with stable incidence and mortality rate of 5% to 10%. The responsible drug for agranulocytosis must be identified, discontinued and permanently contraindicated.